Succes Strategies of Elite First Nations, Inuit, and Métis Athletes - Jacko, Maria J. (2014)
The purpose of this study was to interview elite First Nations, Inuit, and Métis athletes to gain an in-depth understanding of their personal journeys to excellence. Semi-structured interviews were conducted and a narrative analysis was used to analyze the research findings. The three objectives were to find success strategies, obstacles and advice the elite athletes would provide to Aboriginal youth. The main success strategies were found to be Aboriginal elements, focus, mental preparation for competition, parental support, passion, and positive self-talk. Multiple obstacles were faced by the athletes in this study, with racism and leaving home being the commonalities. The advice they provided for young First Nations, Inuit, and Métis athletes was rich and inspiring. The findings of this study provide useful information for aspiring Aboriginal athletes, and for future ongoing meaningful research, that may lead to reducing the gaps in the literature.